Pemanfaatan Pengobat Tradisional oleh Masyarakat - Gitawati, Retno (Jurnal Kefarmasian Indonesia, 2009)
Traditional practitioners Pengobatan Tradisional (Battra) are becoming parts of health care services, and are used to overcome certain health problems in rural areas as well as in urban. However, there is not enough nation wide data of how wide are traditional practices being utilized by the population. Further analysis using the nationwide Riskedas-2007 data is conducted to describe how Battra in Indonesia involved in the population's health care. The analysis is done descriptively, using the cleaned Kesmas (public health) data, ana crosssectional designed with the total sample size of 36.584 respondents. The results showea 1.2% of respondents rely on Battra for inpatient and outpatient services. About 10.1% respondents in West Sulawesi province went to in-patient-serviced (hospitalized) Battra jot their health problems, which is the largest proportion among other Battra utilizations in other provinces. While South Kalimantan is the province with the largest proportion of respondents (4. 7%) went to outpatient services of Battra. Access to the nearest conventional/allopalhic health care services (e.g. public hospital, primary health care, clinics) infuenced the respondent ’s preference for going to Battra The proportion of male respondents who went to Battra is greater than the females, and so the lower educated, and the lower economic status of respondents. More respondents in rural areas went to Battra compared to those in urban.